2017
DOI: 10.1016/j.ultrasmedbio.2017.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler and Microemboli Detection: Relationships to Symptomatic Status and Histopathology Findings

Abstract: The purpose of this study was to determine the relationship between symptomatic status, transcranial Doppler (TCD) microemboli presence and plaque histopathology findings. TCD was performed on 60 subjects (37 symptomatic, 23 asymptomatic) prior to undergoing clinically indicated carotid endarterectomy. The frequency of microemboli signals was not significantly different between symptomatic and asymptomatic subject groups (p=0.88) and there were no differences observed in the macroscopic or histopathology scori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Previously we have demonstrated that patients with advanced carotid atherosclerosis had poorer cognitive performance compared with age‐matched controls and showed a loss from their premorbid IQ regardless of whether they presented with neurologic symptoms (stroke, transient ischemic attack, speech, and motor or visual deficits) . We have also demonstrated that patients with advanced atherosclerosis had similar plaque histopathologic findings at the time of carotid endarterectomy, suggesting that both symptomatic and asymptomatic patients have plaque features that are similar and capable of releasing microemboli . Thus, it becomes imperative to identify new measures, such as CPSIs, to further characterize plaque instability and optimize treatment of carotid atherosclerosis to halt or delay the onset of the cognitive decline associated with vascular disease.…”
Section: Discussionmentioning
confidence: 94%
“…Previously we have demonstrated that patients with advanced carotid atherosclerosis had poorer cognitive performance compared with age‐matched controls and showed a loss from their premorbid IQ regardless of whether they presented with neurologic symptoms (stroke, transient ischemic attack, speech, and motor or visual deficits) . We have also demonstrated that patients with advanced atherosclerosis had similar plaque histopathologic findings at the time of carotid endarterectomy, suggesting that both symptomatic and asymptomatic patients have plaque features that are similar and capable of releasing microemboli . Thus, it becomes imperative to identify new measures, such as CPSIs, to further characterize plaque instability and optimize treatment of carotid atherosclerosis to halt or delay the onset of the cognitive decline associated with vascular disease.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the plaque burden, plaque compositional features of LRNC and IPH are important imaging biomarkers for vulnerable plaque 3,26 . Micro‐disruption of vulnerable plaques with large LRNC or IPH may occur asymptomatically but will lead to obstruction of microcirculation due to the episodic micro‐emboli 27,28 . In addition, the demand for hemodynamic compensation from the contralateral side was increased along with the obstruction of microcirculation and coexisting small vessel disease.…”
Section: Discussionmentioning
confidence: 99%
“…Irregular surface morphology tends to cause flow disruption, which may accelerate thrombus formation on the surface and the microemboli from plaque components might drop into the distal branches of intracranial arteries (39). However, a recent study showed that although microemboli was closely related to plaque ulceration, both symptomatic and asymptomatic patients can have plaque with similar features of instability and the ability to create emboli (40).…”
Section: Carotid Atherosclerotic Plaque Imaging In Strokesmentioning
confidence: 99%